External complexation of BODIPYs by CB[7] improves in-cell fluorescence imaging. Issue 1 (24th November 2021) - Ayhan, Mehmet Menaf; Özcan, Emrah; Alkan, Fahri; Çetin, Metin; Ün, İlker and Bardelang, David and Çoşut, Bünyemin
Abstract : The nonradiative decay processes of BODIPYs can be considerably prevented by complexation with CB[7] to making utmost absorbed excitation energy used for high emission which plays a crucial role in fluorescence labelling and optoelectronic devices. Abstract : Organic luminescent compounds with high emission properties play a crucial role in fluorescence labelling and optoelectronic devices. In this work, we prepared three water soluble BODIPY derivatives (B-4, B-5, and B-6) which are weakly fluorescent due to non-radiative relaxation pathways (charge transfer: CT or heavy atom effect). However, CB[7] significantly improves BODIPY fluorescence by ∼10 fold for B-4, and by ∼3 fold for B-5. The (TD)DFT analyses suggest that for B-4 and B-5, the CT state is blue-shifted as a result of the external binding of CB[7] near the pyridinium groups. This effect favoured a radiative decay through a locally-excited (LE) π→π* transition state of BODIPYs resulting in a CB[7]-induced emission increase in solution (and in the solid state), without compromising singlet-to-triplet intersystem crossing (ISC). The improved emission of the BODIPY·CB[7] complexes was used for the fluorescence imaging of U87 cells illustrating the relevance of this approach. These results suggest that BODIPY·CB[7] complexes could be used as theragnostic agents by combining fluorescence imaging and treatment by photodynamic therapy.